Pendekatan Saintifik Kurikulum 2013 dalam Pembelajaran Bahasa Arab bagi Siswa Tunanetra - Zulfa, Yunita Laila (Departemen Pendidikan Bahasa Arab, 2020)
The purpose of this study was to describe the implementation of Arabic learning for the visually impaired using the scientific approach. This research is descriptive qualitative research with miles and hubermen model data analysis and data validity test using data triangulation. The implementation of the scientific approach for the visually impaired in MTs. Foundation for the Blind Welfare Foundation is different in the observing section, students cannot make observations with the sense of sight so observations cannot deal with video media. Students more often make observations with the sense of hearing with, listen to explanations and use the sense of touch, for media that is used only with braille. However what is unfortunate is very minimal textbooks that form a Braille so that students cannot learn independently.